Taking an elemental approach to the conceptualization and measurement of Machiavellianism, narcissism, and psychopathy. Issue 4 (10th March 2022) - Kay, Cameron S.; Arrow, Holly
Abstract: The study of aversive or 'dark' personality traits (e.g., Machiavellianism, narcissism, and psychopathy) is afflicted by three types of issues. Measures of aversive traits that are meant to assess the same traits often capture different content—an issue of jingle. Measures that are meant to assess different traits often capture near‐identical content—an issue of jangle. Finally, disagreement over what unites aversive personality traits leads to different conclusions about what is and is not an aversive personality trait—an issue of conceptual centrality. This study outlines how decomposing personality traits into smaller elements can address these three issues. It also provides a primer on the history and assessment of these traits and sets an agenda for future research.